Pengaruh Pemberian Pinjaman Berbasis Digital Terhadap Pendapatan Usaha Pada PT. Bank BRI Agro - Aditya Pradana (JURNAL RISET AKUNTANSI JAMBI, 2022)
This study aims to determine whether the effect of digital loan product on Business revenue at PT. Bank BRI AGRO. Data collection uses primary data. The population used was obtained from the digital loan product data, while the sample is 40 data obtained from the research period of 1 year. The analytical method used is a simple linear regression analysis, supplemented by a test of the classical assumptions of normality, multicollinearity, and heteroscedasticity.The results of this study are known in the correlation test (T test) that the significant value of tcount> ttable is 2,440> 2,028. This shows that more and more People's digital loan product given to customers can be put to good use by Business actors for venture capital besides giving People's Business proposed by customers in accordance with their wants and business needs.